“Communication’s Experience and Lived Experience” - Mateus, Samuel (2014)
Building on the meditations of Walter Benjamin around experience and modernity, we ponder the relationship between communication, experience and lived experience. If, on the one hand, the German essayist takes lived experience as impoverished experience, on the other hand, it is argued that the seizure of these lived experiences may just lead us to experience. This idea is developed and applied to communication. It is maintained that Experience (Erfhärung) and Lived Experience (Erlebnis) are not only two experiential qualities going hand in hand, but also, it is contended, contemporary mediatisation is based on the communicability of Lived Experiences, thus contributing to the process of Experience’s constitution.